Людино-машинне керування одновісним двоколісним персональним електричним транспортним засобом за умови лінійного руху - Щур, І. З.; Дзьоба, Т. Я.; Голубовський, П. Й.; Shchur, I. Z.; Dzoba, T. Y.; Holubovskyi, P. Y. (Видавництво Львівської політехніки, 2019)
Розглянуто новий вид персонального електричного транспортного засобу (ЕТЗ) – сегвей, чи гіроборд, у якому користувач під час керування рухом бере безпосередню участь у балансуванні свого положення відносно осі, що з’єднує два колеса з індивідуальними електроприводами. Такий ЕТЗ – складна людино-машинна система, робота якої залежить від команд людини та відповідної реакції системи автоматичного керування (САК) рухом. Тому для розроблення останньої необхідно знати як закономірності роботи електромеханічної системи цього ЕТЗ, так і навички керування, які набув користувач. На основі рівняння Лагранжа ІІ роду розроблено математичну модель кінематики руху такого ЕТЗ у вигляді нелінійної системи взаємозв’язаних диференціальних рівнянь другого порядку. Як системи електроприводів коліс застосовано замкнені за струмами якоря синхронні машини із постійними магнітами, які керуються транзисторними інверторами напруги за положенням їх роторів відповідно до сигналів, отриманих від встановлених на колесах енкодерів. Завдання на електромагнітні моменти приводів коліс формують ПД-регулятори за сигналами від системи давачів – твердотільних гіроскопа та акселерометра, які дають змогу визначити кут нахилу тіла користувача. За розробленою функціональною схемою системи “користувач – гіроборд” у середовищі Matlab/Simulink створено імітаційну комп’ютерну модель, в яку входить розроблена математична модель кінематики руху гіроборда із користувачем. Ця модель імітує поведінку користувача, а також роботу САК електроприводами коліс. Визначено раціональні налаштування регуляторів моделі. У результаті проведеного комп’ютерного симулювання циклу руху гіроборда отримано низку осцилограм основних координат, що описують динаміку системи. Вони дали змогу зрозуміти закономірності взаємодії людини і машини та показали працездатність розроблених підходів до побудови системи керування гіробордом.

The paper deals with a new kind of personal electric vehicle (EV) – a segway or a gyroboard, in which a user, in motion control, takes direct part in balancing of his position with respect to the axis connecting two wheels with self electric drives. Such EV is a complex human-machine system, whose work depends on human commands and on the corresponding reaction of the movement automatic control system (ACS). Therefore, for the development of the latter, it is necessary to know the work regularities of the electromechanical system of this EV, as well as the skills in management acquired by the user. Based on the Lagrange II equation, the mathematical model of the motion kinematics of such an EV in the form of a nonlinear system of interconnected differential equations of the second order is developed. As systems of electric drives of the wheels, synchronous machines with permanent magnets are used and controlled by voltage transistor inverters based on the positions of their rotors in accordance with signals from encoders linked with the wheels. The references on the electromagnetic torques of the wheel drives are formed by the PD regulators based on the signals from the sensor system – solid-state gyroscope and accelerometer, which allow to determine the angle of inclination of the user's body. According to the developed functional scheme of the system “user – gyroboard”, the simulation computer model is created in the environment of Matlab/Simulink, which includes the developed mathematical model of kinematics motion of gyrobord with the user, simulates the behavior of the latter, as well as the work of ACS of wheels electric drives. The rational settings of the regulators are defined from this model. As a result of the computer simulation of the cycle of the gyroboard motion, a series of waveforms of the main variables describing the dynamics of the system was obtained. They made it possible to understand the laws of interaction between user and machine and showed the efficiency of developed approaches to the construction of a gyroboard control system.

1. Jeon D., Hong W.T., Choi H. Smart personal mobility (SPM) for service and entertainment // Proc. 11th ACM/IEEE Int. Conf. on Human-Robot Interaction (HRI), 2016, рр. 557. 2. Govardhan P., Thakre A., Shende N., Phadnis N., Muley S. Survey on self balancing two wheel electric prototype // Int. J. Engineering Research and General Science, 2017, vol. 5, Is. 5, рp. 32–36. 3. Draz M. U., Ali M. S., Majeed M., Ejaz U., Izhar U. Segway electric vehicle // Proc. Int. Conf. Robotics and Artificial Intelligence, 2012, рр. 34–39. 4. Cardozo G. S. S., Vera L. M. S. Prototype for a self-balanced personal transporter // Proc. 2012 Workshop on Engineering Applications, 2012, рр. 1–6. 5. Семенов М. Е., Хатиф З., Решетова О. О., Демчук А. А., Мелешенко П. А. Модель динамики обратного маятника с гистерезисным управлением // Вест. Воронеж. гос. ун-та. Серия: Физика. Математика. 2016. № 4. С. 165–177. 6. Эмирбеков Н. Э., Эмирбеков М. Э. Разработка алгоритмов раскачки и стабилизации обратного маятника, закрепленного на валу двигателя // Автоматика и программная инженерия. – 2016, №1(15). – С. 38–43. 7. Burket M. Segway design project // ІЕЕЕ Trаns. Оn іndustrу аррlісаtіоns. – 2007, vol. 43, Nо. 3, рр. 769–776. 8. Khan M. H., Chaudhry M., Tariq T., Fatima Q.-ul-A., Izhar U. Fabrication and modelling of segway // Proc. 2014 IEEE Int. Conf. on Mechatronics and Automation, August 3–6, Tianjin, China, рр. 280–285. 9. Babazadeh R., Khiabani A. G., Azmi H. Optimal control of Segway personal transporter // Proc. 4th Int. Conf. on Control, Instrumentation, and Automation (ICCIA), 27–28 January 2016, Qazvin, Iran, рр. 18–22. 10. Renet J. Motion control for a two-wheeled vehicle using a self-tuning PID controller // Control Engineering Practice, 2008, vol. 16, рр. 365–375. 11. Miranda J. Application of Kalman filtering and PID control for direct inverted pendulum control // ІЕЕЕ Trаns. Smаrt Ggrіd, 2014, vol. 5, Nо. 2, рр. 944–953. 12. Mohtasib A. M., Shawar M. H. Self-balancing two-wheel electric vehicle (STEVE) // Proc. 9th Int. Symp. on Mechatronics and its Applications (ISMA13), Amman, Jordan, April 9–11, 2013, рр. 1–8. 13. Ahmad S., Siddique N. H., Tokhi M. O. A modular fuzzy control approach for two-wheeled wheelchair // J. of Intelligent & Robotic Systems. – Springer Science+Business Media B. V., 2011, vol. 64, Is. 3–4, рр. 401–426. 14. Kwak S., Choi B.-J. Design of fuzzy logic control system for Segway type mobile robots // Int. J. of Fuzzy Logic and Intelligent Systems, 2015, vol. 15(2), рр. 126–131. 15. Gu D.-W., Petkov P.H., Konstantinov M. M. Robust control of self-balancing two-wheeled robot // Robust Control Design with MATLAB®, Springer, 2018, рр. 435–454. 16. Литвинов О. І. Теоретична механіка. Ч. ІІ. Динаміка. Основи аналітичної механіки / О. І. Литвинов, Я. М. Михайлович, А. В. Бойко, М. Г. Березовий. К.: Агроосвіта, 2013. – 576 с.
Human-machine controlling of one-axis two-wheel personal electric vehicle in the case of liner movement
Keywords: персональний електричний транспортний засіб; сегвей; гіроборд; самобалансування; людино-машинна система; personal electric vehicle; segway; gyroboard; self-balancing; human-machine system; 62-83-52; 621.313.3